Implementasi Manajemen Peserta Didik dalam Meningkatkan Kedisiplinan Anak di TK Islam Baiturrahman Jombang Ciputat - Alipiya Azzahra; Surip Surip; Singgih Aji Purnomo (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2026)
This study aimed to describe the implementation of student management models in improving student discipline at TK Islam Baiturrahman Jombang, Ciputat, South Tangerang. This research used a qualitative approach with a descriptive method. The research subjects consisted of the principal, teachers, students, and parents. Data were collected through observation, interviews, and documentation, while data analysis used the Miles and Huberman model. The results showed that the implementation of student management was carried out through disciplinary habituation, supervision, teacher role modeling, and collaboration with parents. The forms of discipline applied included time discipline, behavioral discipline, learning discipline, and worship discipline. Supporting factors included a conducive school environment and consistent habituation, while inhibiting factors included differences in student characteristics and lack of discipline habituation at home.